Pengaruh Earning Per Share Terhadap Return Saham Sektor Telekomunikasi - Akbar, Aswin; Nurhayati, Nurhayati (Sains: Jurnal Manajemen dan Bisnis, 2025)
This study aims to analyze the effect of Earning Per Share (EPS) on stock returns in the telecommunications sector listed on the Indonesia Stock Exchange (IDX) during the 2014–2023 period. EPS is a key financial performance indicator theoretically believed to influence investment decisions and stock price movements, yet previous studies have yielded inconsistent results. Using a quantitative approach and panel data regression method, the study analyzed 60 observations from 6 purposively selected companies. Model selection was conducted through Chow, Hausman, and Lagrange Multiplier tests, which indicated that the Random Effect Model (REM) was most appropriate. The regression results revealed that EPS had no significant effect on stock returns (p = 0.5470; R² = 1.08%). These findings suggest that EPS is not a primary predictor of stock returns in the telecommunications sector. Therefore, investors are encouraged to consider other fundamental indicators and sector-specific dynamics when making investment decisions.